O novo papel do Superior Tribunal de Justiça como corte de precedentes: uma análise dos recursos especiais repetitivos - Costa, Jéssica Chaves (2019)
The purpose of this paper is to analyze the "new" role of the Superior Court of Justice, as Court of Precedents, a Supreme Court whose purpose is to standardize and give meaning to federal infraconstitutional law. In this way, we will observe the theoretical and philosophical foundations that allow the characterization of a court as supreme, in addition to analyzing, more slowly, the Superior Court of Justice, the institute of the special resource and its repetitive modality. In addition, it will be investigated to what extent the consolidation of precedents and the improvement of the regulation of the institute of repetitive special resources contributes to this new profile, in that they collaborate directly for the coherence and unity of law. Finally, we will try to establish the reflexes that the special repetitive resource projects in the configuration of the current Superior Court of Justice, and, above all, the impact of its adoption in our political-legal system as a whole.